Urbanism and our urban future - Samalavicius, Almantas (Journal of Architecture and Urbanism, 2013)
Professor, Doctor almantas Samalavicius interview with Witold rybczynski,architect, urbanist and architectural writer, Emeritus Professor of the university of PennsylvaniaThe last century was marked by the proliferation of modernism and many of its varieties have left lasting marks on architecture as well as contemporary cities, however, this legacy and its present forms produce ambiguous affects on architectural practices as well as on city-building. The legacy, or perhaps it is much better to call it legacies – of modernism so far remains rather controversial and sparkles ongoing debates not only among architects, theorists and critics of architecture, but affects wider layers of society, these days preoccupied with architectural and urban issues.Witold Rybcynski – an architect, urban historian as well as prolific and renowned architectural writer and author of numerous books that have been translated to many languages is professor emeritus of Pennsylvania University and co-founder of Wharton Real Estate Review. He has contributed a lot to the understanding of architectural legacy as well as it contemporary trends. A stimulating and thoughtful writer, he has discussed various aspects of architecture, urbanism and city-life that are important to architects, architectural academy and society at large. This conversation was stimulated by his writings as well as need to reconsider historical issues.